Strengthening banks' market discipline and leveling the playing field: Are the two compatible? - Sironi, Andrea (Journal of Banking & Finance, 2002)
This paper examines whether the supervisory objective of strengthening market discipline is compatible with the one of enhancing competitive equality for internationally active banks. This issue is empirically investigated by comparing the determinants of major US and European banks' subordinated notes and debentures (SND) spreads. Three main results emerge. First, the spread/rating relationship is both statistically significant and very similar for US and European banks' bonds. Second, US banks tend to pay a higher average spread on their SND issues because of a poorer average rating. This is due to the presence of European public sector banks, i.e. banks which are either government owned or benefit from explicit government guarantees. In fact, US banks have slightly better Moody's bank financial strength and FitchIBCA individual average ratings, which omit the influence of government and other external support on risk borne by investors. Finally, controlling for the issuing banks' default risk, US banks pay a statistically significant lower average spread on their SND issues. This result is attributed to the higher liquidity of the US market for banks' bonds.